Choosing people: the role of social capital in information seeking behaviour - Catherine A. Johnson (Information Research: An International Electronic Journal)
It is an almost universal finding in studies investigating human information behaviour that people choose other people as their preferred source of information. An explanation for the use of people as information sources is that they are easier to approach than more formal sources and therefore are a "least effort" option. However there have been few studies that have investigated who the people chosen as information sources are and what their relationship to the information seeker is. This paper reports findings that come out of a larger investigation of the information seeking behaviour of a random sample of residents of Ulaanbaatar, Mongolia. Using the theory of social capital as a conceptual framework and the methods of social network analysis, this study investigated the relational factors associated with the choice of people as information sources. Results indicate that respondents chose people who had better resources than they had and were not well known by them. This suggests that respondents were deliberate in their choice of people information sources and therefore it is speculated that people are not necessarily the least effort option but may require considerable effort to seek out and consult.